MULTICULTURAL EDUCATION TRANSFORMATION: BUILDING SOLIDARITY, TOLERANCE AND GLOBAL PEACE THROUGH THE GLOBAL CITIZENSHIP EDUCATION (GCED) - Mujiburrohman, Mujiburrohman; Faqih, Moh. Mahfudz (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study aims to analyze the implementation of multicultural education and Global Citizenship Education (GCED) in fostering solidarity, tolerance, and global peace at Pondok Pesantren Nurul Jadid in Paiton, Probolinggo. The pesantren hosts students from diverse cultural, ethnic, religious, and national backgrounds, including Indonesia, Malaysia, and Thailand. The research employs a qualitative approach, with data collection techniques including in-depth interviews, observations, and document studies involving various research subjects, namely the pesantren leadership, teaching staff, guardians, and students. The collected data are analyzed using Miles, Huberman, and Saldana's data analysis techniques, which involve data reduction, data presentation, and drawing conclusions. The results show that the implementation of multicultural education and GCED at Pondok Pesantren Nurul Jadid has successfully created an inclusive environment where students learn to appreciate differences and develop solidarity among themselves. Cultural attribution, the internalization of multicultural values, and behaviors supporting diversity have been applied in the students' daily activities through various programs such as cultural discussions, communal work projects, and social activities. However, challenges such as inter-ethnic conflicts and bullying persist, requiring more effective policies and approaches for resolution. In conclusion, the implementation of multicultural education and GCED at Pondok Pesantren Nurul Jadid has had a positive impact in strengthening solidarity, tolerance, and peace among students. However, for the sustainability and development of this program, continuous evaluation and improvement are necessary, as well as increased collaboration among stakeholders to create a generation that is not only sensitive to diversity but also actively contributes to global peace and well-being